Synthesis and Characterization of TiO2/Ni for Photoelectrochemical Dopamine Sensors - Irhamni Irhamni; Jarnuzi Gunlazuardi; Rahmat Wibowo (EduChemia: Jurnal Kimia dan Pendidikan, 2026)
Dopamine (4-(2-aminoethyl) benzene-1,2-diol) is an essential biomarker for the diagnosis of neurological disorders. Owing to the increasing prevalence of diseases associated with low dopamine levels, the development of fast and simple detection methods has become crucial. The photoelectrochemical method offers significant advantages for dopamine sensors because of its minimal instrumentation and simple sample preparation. In this study, the synthesis of TiO₂ nanotubes and their morphological, optical, and photoelectrode properties under different synthesis conditions were investigated. Additionally, the effect of Ni nanoparticle deposition on TiO₂ via cyclic voltammetry (CV) electrodeposition is examined in terms of optical absorption shift and photoelectrode activity. Self-aligned TiO₂ nanotubes with a length of 2.2 µm, a diameter of 62 nm, and a wall thickness of 48 nm were synthesized via anodization using a Ti wire in an ethylene glycol/NH₄F electrolyte. The results show that the linearity range of the photoelectrode is 0.01–100 µM, with a detection limit of 4.8 µM and a quantification limit of 14.6 µM. These results demonstrate that Ni-decorated TiO2 nanotube photoelectrodes exhibit enhanced photoelectrochemical performance and are promising candidates for sensitive and reliable dopamine detection.